Measurement and modelling of noise-power-distance curves of a fixed-wing UAV - Amargianitakis, Daniel C.; Self, Rod; Proenca, Anderson R.; Boyd, Cameron; Westcott, Oliver; Ferraro, Mario; Erbil, Mehmet Ali; Entwistle, Robert (American Institute of Aeronautics and Astronautics (AIAA), 2022)
This paper presents an investigation into the noise produced by an unmanned aerial vehicle (UAV). The platform used, `Spotter', is a fixed-wing, light UAV comprising a 4-meter wingspan. Spotter was originally designed to perform long-endurance, all-weather patrol missions in coastal and maritime environments. This vehicle has been continuously upgraded and is now used in a broader range of applications. Increasing demand by research and industrial partners, as well as the UK Civil Certification Authority (CAA) has led to a survey of the Spotter's in-flight noise footprint. The CAA Operating Safety Case of this platform is currently being updated and the major findings are presented in the paper. Preliminary results were obtained in flight tests performed at the Draycot Aerodrome over two expeditions in the summer of 2021, in the UK. A series of flyovers, takeoff and landing operations were measured. Flyovers were performed at constant altitude at series of power settings, incrementing from low to maximum power output. These measurements are then used to generate Noise-Power-Distance curves for the Spotter UAV. Static directivity characteristics of the dual propeller setup were also measured, with intent of feeding into future airport exposure studies.
Keywords: Aeroacoustics